Comparative 3-dimensional kinematic analysis of snatch technique between top-elite and sub-elite male weightlifters in 69-kg category - Liu, G.; Fekete, G.; Yang, H.; Ma, J.; Sun, D.; Mei, Q.; Gu, Y. (Heliyon, 2018)
Objective: The purpose of this study was to determine the differences in technical characteristics between top-elite and sub-elite male weightlifters performing the snatch style in the 69-kg category. The obtained results can provide valuable information for lower level lifters and coaches to achieve better competition performance by altering their training methods accordingly. Methods: Six top-elite and six sub-elite weightlifters participated in this study. The heaviest successful snatch lift from the three attempts of each subject was analyzed. The video data were recorded under competition conditions at China National Weightlifting Championship and China Olympic Trial, which were analyzed by SIMI°Motion7.50 3D analysis system. Results: The results showed that the maximum vertical- and relative vertical height (normalized by athletes' height) of the barbell, the maximal vertical linear velocity and acceleration of the barbell were significantly greater in top-elite lifters (p < 0.05). In addition, the flexion angles of the knee joint were significantly greater in top-elite lifters during the first phase and the third phase of the snatch lift. Sub-elite lifters showed less flexion and significantly slower angular velocity in knee joint than top-elite lifters during the second phase of the snatch lift (p < 0.05). Conclusion: The findings of the present study demonstrated the differences in technical characteristics between the two levels. According to these findings, coaches of sub-elite lifters should focus on exercises suitable to the strength characteristics of the first and the third phase of the snatch lift. In addition, the flexor muscles of knee joint among the sub-elite lifters should be strengthened and the ability of generating and utilizing elastic energy during the second phase of the snatch lift should be improved.